Harmonizing Cognition and Communication: Implementing the Natural Approach for EFL Young Learners - Nayla Sabrina; Nishfa Auranissa Rachman; Palqi Wijdani; Dedi Sulaeman (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study aims at the implementation of a Natural Approach in teaching English to young learners aged 7–12, highlighting the im-portance of pedagogical practices that correspond to their develop-mental and cognitive characteristics. Drawing on Stephen Krashen’s second language acquisition framework—especially the emphasis on comprehensible input and maintaining a low affective filter—the re-search applies a teaching model that incorporates repetitive melodic chants (“vocab yells”), a grammar-free oral production stage, and thematic vocabulary-based games. In this study, we use qualitative results to indicate that this combination strengthens rhythmic and auditory reinforcement, encourages communicative confidence by removing the burden of grammatical accuracy, and supports con-sistent mastery through enjoyable, repeated activities. The findings showed that an instructional approach prioritizing meaningful in-put and positive emotional conditions over formal correctness can effectively facilitate naturalistic language development. This model not only lays a strong foundation for early English proficiency but also nurtures a positive and confident attitude toward language learning, offering valuable insights for curriculum development and classroom practices in EFL settings for children.